Confronting chronic shocks: Social resilience in Rio de Janeiro's poor neighborhoods. (April 2020) - Fahlberg, Anjuli; Vicino, Thomas J.; Fernandes, Ricardo; Potiguara, Viviane
Abstract: While much of the literature on social resilience is concerned with how cities overcome "shocks" to the urban system, much less is known about the strategies of survival and adaptation among its poorest residents. We argue that residents in poor, often informal, neighborhoods are faced with chronic shocks, or constantly recurring disasters, such as floods, severe illness, or violent police invasions. In this paper, we draw on focus groups, participant-observation and a survey ( n  = 989) based on a participatory action research methodology in Cidade de Deus, one of Rio de Janeiro's poor neighborhoods (or "favelas"). We examine how concentrated poverty and violence affect residents' well-being and survival strategies. We find that residents in these areas address chronic shocks along varying levels of: (1) 'formality, ' or engagement with the state apparatus or formal economy; (2) contentious politics; and (3) collectivity, from addressing the needs of the individual or kinship network to the neighborhood. We conclude that the variability in strategies reflects residents' ability to adapt to an uneven and unjust urban environment. Poor residents seek the same rights, resources, and privileges of other urban citizens. Highlights: The urban poor face chronic shocks, or constantly recurring disasters in a context of poverty, fragility and violence. Poor urban residents deal with chronic shocks along varying levels of: (1) formality; (2) contention; and (3) collectivity. Participatory action research helps to identify the concerns and resilience strategies of the urban poor. Residents in Cidade de Deus, Rio de Janeiro must constantly navigate between multiple strategies of social resilience. Policymakers should not expect the poor to be resilient, but provide them the same resources as other urban citizens.